Flexural Behavior of Concrete Beams Reinforced with FRP Bars Under Long Exposure to UAE Environment - Alkhraisha, Hakem (2021)
A Master of Science thesis in Civil Engineering by Hakem Mohammad Alkhraisha entitled, “Flexural Behavior of Concrete Beams Reinforced with FRP Bars Under Long Exposure to UAE Environment”, submitted in March 2021. Thesis advisor is Dr. Farid Abed. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).